Postwar British literature and postcolonial studies - MacPhee, Graham, 1968- (Postcolonial literary studies., 2011)
Places literary developments within an expanded conception of the legacy of imperialism and decolonisation. This radical reassessment shows how, after the Second World War, British national identity and culture was shaped in ways that still operate today. As empires declined, globalisation spread, and literature responded to these influences. As Graham MacPhee explains, postwar writers blended the experimentalism of prewar modernism with other cultural traditions. In this way, they reveal both the pain and the pleasures of multiculturalism, as they seek to cope with the shock of post-imperial downsizing. Case studies include:. Sam Selvon's The Lonely Londoners John Arden's Serjeant Musgrave's Dance Linton Kwesi Johnson's Dread Beat an' Blood Tony Harrison's V Kazuo Ishiguro's The Remains of the Day Leila Aboulela's Minaret Andrea Levy's Small Island Ian McEwan's Saturday Key Features. Explores concepts and critical terms such as 'British national literature', 'new ethnicities', 'migrancy', 'hybridity', 'Western hegemony' and 'globalisation' Discusses a wide range of writers, from Auden, Orwell and T.S. Eliot to Philip Larkin and Tony Harrison Resources for students and researchers include a timeline and suggestions for further reading